2015
DOI: 10.1093/jxb/erv123
|View full text |Cite
|
Sign up to set email alerts
|

C4bioenergy crops for cool climates, with special emphasis on perennial C4grasses

Abstract: There is much interest in cultivating C4 perennial plants in northern climates where there is an abundance of land and a potential large market for biofuels. C4 feedstocks can exhibit superior yields to C3 alternatives during the long warm days of summer at high latitude, but their summer success depends on an ability to tolerate deep winter cold, spring frosts, and early growth-season chill. Here, we review cold tolerance limits in C4 perennial grasses. Dozens of C4 species are known from high latitudes to 63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 113 publications
0
30
1
Order By: Relevance
“…Switchgrass ( Panicum virgatum L.) is a native North American perennial prairie grass mostly known for its use as a biofuel feedstock. The high biomass production, low input requirements, and its ability to be productive on marginal land are some features that make switchgrass an attractive cellulosic feedstock [ 1 , 2 ]. However, the high degree of lignification of secondary cell walls (around 20% of switchgrass dry cell wall biomass) inhibits biomass conversion to fermentable sugars and biofuel in switchgrass, which, in turn, is an economic barrier to biofuel production [ 1 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Switchgrass ( Panicum virgatum L.) is a native North American perennial prairie grass mostly known for its use as a biofuel feedstock. The high biomass production, low input requirements, and its ability to be productive on marginal land are some features that make switchgrass an attractive cellulosic feedstock [ 1 , 2 ]. However, the high degree of lignification of secondary cell walls (around 20% of switchgrass dry cell wall biomass) inhibits biomass conversion to fermentable sugars and biofuel in switchgrass, which, in turn, is an economic barrier to biofuel production [ 1 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two major factors are air and soil temperatures during the winter and early spring following establishment (Hasting et al, 2009). Several previous studies have reported lethal M. × giganteus rhizome kill (>50%) during the first winter if soil temperatures drop below about −3.4 to −4.0 • C (Clifton-Brown and Lewandowski, 2000;Clifton-Brown et al, 2001;Kucharik et al, 2013;Friesen et al, 2015;Peixoto et al, 2015;Sage et al, 2015). However, some reports indicate that first-year M. × giganteus stands have consistently withstood harsher winter conditions; air temperatures as cold as −20 • C and soil temperatures as low as −6 • C (Heaton et al, 2010;Friesen et al, 2015).…”
Section: Winter Survivalmentioning
confidence: 99%
“…Perennial C 4 grass species have garnered the most attention as candidate dedicated biomass crops, particularly the C 4 species, switchgrass and Miscanthus. Although they are warmseason species, they are adapted to Ontario conditions (Sage et al 2015). They also have attributes required for sustainable biomass crop production: perennials with a 20+ year expected stand longevity, high yield potential (Heaton et al 2004), low input requirements, utilize existing commercial equipment for production ( Figs.…”
Section: Dedicated Biomass Cropsmentioning
confidence: 99%
“…It has been estimated that 5% of all arable land (i.e., Class 1-5 lands) could provide over 2 million t yr −1 of dry matter of either switchgrass or Miscanthus biomass (Kludze et al 2013a). Due to higher yield potential, resulting from duration of leaf area as well as cold tolerance (Sage et al 2015), a Miscanthus biomass system compared with a switchgrass biomass system would require a lower percentage of available land area to produce an equivalent amount of biomass.…”
Section: Dedicated Biomass Cropsmentioning
confidence: 99%